A detailed pituitary profile always matters. (27th January 2023) - Helmy Assaad Khalil, Ramy Samir
Abstract: 29-year-old female with known hypothyroidism and positive thyroid auto antibodies, followed up throughout pregnancy for adjusted doses of thyroid replacement therapy, presented 2 months post-partum with gradually increasing fatigue, repeated pre-syncope experience, inability to cope with daily home and family needs and headache. Adequacy of thyroid replacement therapy was questioned, TSH has been performed: 0.18 mIU/ml. Checking the blood pressure in lying and standing position has showed Postural hypotension. An urgent measurement of Cortisol (am) showed a result of1.06 ug/dl. Preliminary Differential Diagnoses have been suggested; Pituitary apoplexy, Pituitary adenoma, Autoimmune adrenalitis (Autoimmune Polyglandular Syndrome) or Others. On further detailed history, the patient affirmed dizziness and fainting liability on standing from lying position, bitemporal headache more in the morning. However, she denied frequent urination throughout the day, neither repeated times at night. In addition, she confirmed efficient breast feeding. Continued Lab investigations : ACTH (am) (Low); FT4 (Low; on replacement therapy); IGF1 (Normal) Serum osmolality (Normal); Urine osmolality (Normal); E2 / LH / FSH (normal physiological levels) Prolactin (normal for breast feeding) MRI pituitary and sella: Diffuse isointense enlargement of anterior pituitary gland. Homogenous and strong diffuse pituitary enhancement with gadolinium contrast. History and investigations were not fully matching with any of the previously proposed differential diagnoses, especially in regards of selective corticotroph and thyrotroph affection, sparing other pituitary cell types. Moreover, the autoimmune predisposition, the nature of the clinical presentation and its timing during early postpartum period, together with the laboratory and imaging investigations were all matching with the diagnosis of Lymphocytic Hypophysitis . The Patient got pregnant again 14 months post-partum, reflecting spared gonadotroph function and highlighting the importance to identify this uncommon diagnosis and to notify the patient about normal gonadal function and the normal possibility of pregnancy. However, she remained on hydrocortisone and thyroxine replacement. Finally, it is important that this condition should not be misdiagnosed in the first place as postpartum thyroid disturbance and TSH results, especially during and after pregnancy, shall always be interpreted in the clinical context and with the overall thyroid profile.